Systemwide Clinical Ultrasound Program Development: An Expert Consensus Model - Strony, Robert; Marin, Jennifer; Bailitz, John; Dean, Anthony; Blaivas, Mike; Tayal, Vivek; Raio, Chris; Liu, Rachel; Woods, Aimee; Zwank, Michael; Fields, Matthew; Abo, Alyssa; et al. (The western journal of emergency medicine, 2018)
Clinical ultrasound (CUS) is integral to the practice of an increasing number of medical specialties. Guidelines are needed to ensure effective CUS utilization across health systems. Such guidelines should address all aspects of CUS within a hospital or health system. These include leadership, training, competency, credentialing, quality assurance and improvement, documentation, archiving, workflow, equipment, and infrastructure issues relating to communication and information technology. To meet this need, a group of CUS subject matter experts, who have been involved in institution- and/or systemwide clinical ultrasound (SWCUS) program development convened. The purpose of this paper was to create a model for SWCUS development and implementation.